Shubnikov-de Haas oscillations, peaks and different temperature regimes of the diagonal conductivity in the integer quantum Hall conductor - Gvozdikov, V.M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2005)
A theory for the Shubnikov—de Haas oscillations in the diagonal conductivity sxx of a 2D conductoris developed for the case when electron states within the broaden Landau levels are localizedexcept the narrow stripe in the center. The standard Shubnikov—de Haas oscillations takeplace only in the low-field region which at higher magnetic fields crosses over into peaks. In thelimit Wt >> 1 peaks in the sxx became sharp and between them sxx → 0 (W is the cyclotron frequency, t is the electron scattering time). The conductivity peaks display different temperature behavior with the decrease of temperature, T: a thermal activation regime, sxx µexp(-D/T), which holds at higher temperatures, crosses over into the variable-range-hopping regime at lower temperatureswith sxxµ1/Texp(-√ T0/T)(the prefactor 1/T is absent in the conductance).